SPIRITUALITY OF FAMILIES WITH A LOVED ONE IN END-OF-LIFE SITUATION - Miqueletto, Marcelo [UNESP]; Silva, Lucia; Figueira, Crislaine Barros; Santos, Maiara Rodrigues dos; Szylit, Regina; Faria Ichikawa, Carolliny Rossi de (Univ Santander, 2017)
Introduction: End-of-life care should be marked by the re-appraisal of the spiritual dimension. Objective: This work sought to understand the role of spirituality in the lives of families with a loved one in end-of-life situation. Materials and Methods: This qualitative research was conducted through semi-structured interviews with 15 relatives of patients with serious diseases cared for in the primary health care network in Sao Paulo, Brazil. The data were organized and analyzed according to the methodological figures of the Collective Subject Discourse technique. Results: Spirituality represents a unique role for the families, as it helps to give meaning to life experiences, above all those directly involved with disease and death. However, they find no space to express those issues with the health professionals, with whom they should have a bond and co-responsibility for care based on integrality. Discussion and Conclusions These families recognize spirituality as a strengthening element against difficulties confronted with the illness, but strongly depend on the health staff's availability to increase their experience.
Keywords: Spirituality; Religion; Family; Palliative Care; Death